Selective synthesis of partial glycerides of conjugated linoleic acids via modulation of the catalytic properties of lipases by immobilization on different supports. (15th April 2018) - Verdasco-Martín, Carlos M.; Garcia-Verdugo, Eduardo; Porcar, Raul; Fernandez-Lafuente, Roberto; Otero, Cristina
Highlights: Lipase immobilization via interfacial activation. Improved selective synthesis of partial glycerides of CLA. Modulation of lipases regioselectivity via immobilization. Abstract: Lipases B from Candida antarctica (CALB), Rhizomucor miehei (RML) and Thermomyces lanuginosus (TLL) were immobilized on octadecyl methacylate (OM) or octadecyl methacrylate (OMC) beads. Their specific activity and regioselectivity were studied in the synthesis of conjugated linoleic acid (CLA) partial glycerides, which presented nutraceutical properties. TLL derivatives were poor catalysts. Novozym® 435 was much better than Lipozyme® RM IM. RML activity (a GRAS enzyme) was modulated via immobilization. After only 3 h, OM−RML gave the highest CLA conversion (54% at 40 °C with 1:3 M ratio of glycerol to CLA). OM-RML reduced by a factor of 3.12 and 1.16 the activation energy of the reaction with Lipozyme® RM IM and Novozym® 435, respectively. The new GRAS preparation OM-RML brings forth an optimal regioselective preparation of sn -1 mono and sn -1, 3 diacylglycerols rich in CLA, with a ratio of sn -1, 3/ sn -1, 2 regioisomers of 21.8, compared to 2.3 for Novozym® 435.